Single-Cell TCR Sequencing Reveals the Dynamics of T Cell Repertoire Profiling During Pneumocystis Infection - Yang, Hu-Qin; Wang, Yi-Shan; Zhai, Kan; Tong, Zhao-Hui (Frontiers in Microbiology, 2021)
T cell responses play critical roles in host adaptive immunity against Pneumocystis. However, the dynamics and diversity of the T cell immune repertoire in human immunodeficiency virus (HIV)-negative Pneumocystis pneumonia remains unclear. In this study, single-cell RNA and single-cell T cell receptor (TCR) sequencing were applied to cells sorted from lung tissues of mice infected with Pneumocystis. Our findings demonstrated the clonal cells were mainly composed of CD4+ T cells in response to Pneumocystis, which were marked by highly expressed genes associated with T cell activation. Mice infected with Pneumocystis showed reduced TCR diversity in CD4+ T cells and increased diversity in CD8+ T cells compared with uninfected controls. Furthermore, Th17 cells were mostly clonal CD4+ T cells, which exhibited the phenotype of tissue-resident memory-like Th17 cells. In addition, Pneumocystis-infected mice showed biased usage of TCRβ VDJ genes. Taken together, we characterized the transcriptome and TCR immune repertoires profiles of expanded T cell clones, which demonstrate a skewed TCR repertoire after Pneumocystis infection.